Advancing Muslim-Christian Dialogue Today (American Journal of Islam and Society, 2008)
Books Reviewed: Philip Jenkins, God’s Continent: Christianity, Islam, andEurope’s Religious Crisis. Oxford and New York: Oxford University Press,2007; Jane Idleman Smith, Muslims, Christians, and the Challenge ofInterfaith Dialogue. Oxford and New York: Oxford University Press, 2007;Irfan A. Omar, ed., A Muslim View of Christianity: Essays on Dialogue byMahmoud Ayoub. Maryknoll, New York: Orbis, 2007.Not surprisingly, the Archbishop of Canterbury’s recent comments aboutintegrating more of Shari`ah law within the United Kingdom’s legal systemraised a firestorm of protest in Britain and in many parts of the world. Yetfor twenty-five years already, Britain’s Muslims have been using Shari`ahlaw in community arbitration; by simply adding elements of Islamicjurisprudence in family matters, Muslims would be able to settle mostdivorce cases through arbitration, thus freeing up already congested divorcecourts. Why is this suggestion so outrageous?The only explanation for the deluge of complaints has to do with thesuper-charged and dangerously polarized socio-cultural and religious atmosphereof the “West” in the 2000s. Besides 9/11, other events have contributedto the ratcheting-up of Muslim-European tension: the Danish cartoon saga;the assassination of Dutch filmmaker Theo Van Gogh; the London bombings;the “Fitna” film; and, most recently, the tendentious DVD distributedto nearly 30 million American households in swing states during the presidentialcampaign, “Obsession: Radical Islam’s War Against the West.” Withright-wing politicians determined to raise the specter of “Islamofascism,” anymention of including aspects of the Shari`ah in “enlightened” secular legalstructures is enough to give some people fits of panic.Yet this is the context in which we must insert the three books underreview, each of which examines a particular aspect of today’s vastly complexMuslim-Christian relationship. Philip Jenkins marshals his consider ...